A MAYAN FOUNDER MUTATION IS A COMMON CAUSE OF DEAFNESS IN GUATEMALA - Carranza, Claudia (Clin Genet, 2015)
Over 5% of the world population have varying degrees of hearing loss. Mutations in GJB2 are the most common cause of autosomal recessive non-syndromic hearing loss (NSHL) in many populations. The frequency and type of mutations are influenced by ethnicity. Guatemala is a multi-ethnic country with four major populations: Maya, Ladino, Xinca, and Garifuna. To determine the mutation profile of GJB2 in a NSHL population from Guatemala, we sequenced both exons of GJB2 in 133 unrelated families. A total of six pathogenic variants were detected. The most frequent pathogenic variant is c.131G>A (p.Trp44*) detected in 21 of 266 alleles. We show that c.131G>A is associated with a conserved haplotype in Guatemala suggesting a single founder. The majority of Mayan population lives in the west region of the country from where all c.131G>A carriers originated. Further analysis of genome-wide variation of individuals carrying the c.131G>A mutation compared to those of Native American, European, and African populations shows a close match with the Mayan population.